2017
DOI: 10.1016/j.infsof.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutant reduction based on dominance relation for weak mutation testing

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…[131] explored the program path space and selected mutants that are as diverse as possible with respect to the paths covering them. Gong et al [132] selected mutants that structurally dominate the others (covering them results in cover-ing all the others). This work aims at weak mutation and attempts to statically identify dominance relations between the mutants.…”
Section: Mutant Reduction Strategiesmentioning
confidence: 99%
“…[131] explored the program path space and selected mutants that are as diverse as possible with respect to the paths covering them. Gong et al [132] selected mutants that structurally dominate the others (covering them results in cover-ing all the others). This work aims at weak mutation and attempts to statically identify dominance relations between the mutants.…”
Section: Mutant Reduction Strategiesmentioning
confidence: 99%
“…Sun et al (2017) suggested selecting mutants that are diverse in terms of static control flow graph paths that cover them. Gong et al (2017) used code dominator analysis in order to select mutants that, when they are covered, maximize the coverage of other mutants. This work applies weak mutation and attempts to identify dominance relations between the mutants in a static way.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous research [27], we transformed the mutants into the mutant branches to reflect whether the corresponding mutants are weakly killed or not, and formed a new program by inserting all the mutant branches into the original program; and the nondominated ones, corresponding to the mutants after reduction, were obtained after analyzing the dominance relations among the mutant branches. Our previous method can further improve the weak mutation testing by only covering the nondominated mutant branches, and the generated test cases can cover all the mutant branches, that is, weakly kill all the mutants.…”
Section: Correlation Analysismentioning
confidence: 99%